Booked to die - Dunning, John, 1942- (New York Pocket Books, 1993)
Cliff Janeway, a burnt-out Colorado cop and rare book collector, investigates the murder of his book scout friend, who was tracking down a valuable find when his life was brought to an abrupt conclusion
Originally pubished: New York : Scribner's, c1992.
Keywords: Rare books -- Fiction; Denver (Colo.) -- Fiction; Mystery fiction